The rule of law under siege : selected essays of Franz L. Neumann and Otto Kirchheimer - Scheuerman, William E., 1965- (Weimar and now, 1996)
In the pathbreaking essays collected here, Neumann and Kirchheimer demonstrate that the death of democracy and the rise of fascism during the first half of the twentieth century suggest crucial lessons for contemporary political and legal scholars. The volume includes writings on constitutionalism, political freedom, Nazism, sovereignty, and both Nazi and liberal law. Most important, the Frankfurt authors point to the continuing efficacy of the rule of law as.